Occupation of termite epigeal and arborous nests in a fragment of hypoxerophytic Caatinga in Bom Jesus, Piaui State, Brazil - Núñez, Brenda Nury Costa; Lima, Mauro Sergio Cruz Souza; Menezes, Euripedes Barsanulfo; Pederassi, Jonas (Comunicata Scientiae, 2011)
The process of occupation in Northeast of Brazil started in the coast and internalized itself due to the development of extractive and agricultural production affecting caatinga biome. The expansion of land use, that accompanies the growth of human population, results in fragmentation of natural habitats with the formation of forest fragments of different sizes and shapes. Termites have fundamental importance in ecosystems due to their nesting and feeding behavior by exerting a strong influence on the processes of decomposition in nutrient cycling and on physical and chemical properties of soil. This study aimed to understand, to record and to supplement the understanding of the natural history of this group in Caatinga hypoxerophytic. The collection area comprises a hectare of preserved fragment, where collections were made straight across the area through the linear transect method, measurements of height, circumference, distance from the floor and girth in all nests of the hectare were taken. We identified 10 species belonging to 07 genera of the family Termitidae. They were distributed among the sub-families: Nasutitermitinae (Constrictotermes cyphergaster, Nasutitermes sp1, Nasutitermes sp2, Labiotermes longilabius, Armitermes sp., Syntermes wheeleri and Syntermes molestus) and Termitinae (Spinitermes sp., Inquilinitermes fur and Inquilinitermes microcerus). Regarding the dominance of species in sampled nests in the area, there were three species eudominantes C. cyphergaster, Nasutitermes sp1, S. wheeleri and a subdominant: Nasutitermes sp2. Among the food groups, xilófagous, humus feeding species, grass and litter feeding species and Intermediates have been found.